BENEFITS OF PHYSICAL ACTIVITY ON REPRODUCTIVE HEALTH FUNCTIONS IN WOMEN POLYCYSTIC OVARY SYNDROME: SYSTEMATIC REVIEW - Rahayu, Linda Sri; Dwiningsih, Sri Ratna (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
Polycystic ovary syndrome (PCOS) is a predominant endocrine disorder in women of reproductive age. The prevalence of PCOS is estimated to be around 8-13% of women of childbearing age and up to 70% of cases are undiagnosed. This systematic review aims to synthesize evidence on the impact of physical activity on reproductive health function in PCOS women. Conducted using electronic data base from journals that have been published in PubMed, Science Direct and Wiley. This study investigated physical activity interventions with intensity and volume and measured reproductive function as well as hormonal and menstrual improvements. The inclusion of physical activity alone or combined with other therapeutic interventions improved reproductive outcomes. Reproductive function of women with PCOS can be improved by physical activity. Physical activity can also reduce infertility and social and psychological stress in women.